Platypnoea–orthodeoxia syndrome in COVID-19 - Aayilliath K, Adarsh (BMJ Case Rep, 2021)
Platypnoea–orthodeoxia syndrome (POS) is a rare entity characterised by respiratory distress and/or hypoxia developing in the sitting/upright posture, which is relieved in the supine posture. It is caused by cardiac, pulmonary and non-cardiopulmonary diseases. COVID-19 can have varying respiratory manifestations including acute respiratory distress syndrome (ARDS) and sequelae-like pulmonary fibrosis. POS has been rarely reported in patients with COVID-19. Here we report a case of POS in a patient recovering from severe COVID-19 ARDS. As he was gradually mobilised after his improvement, he had worsening dyspnoea in the sitting position with significant relief on assuming a supine posture. He was diagnosed with POS after ruling out other causes of POS. He was treated with oxygen support in upright posture and chest physiotherapy was continued, to which he showed improvement. POS is a rare manifestation of COVID-19 which needs awareness as it can be diagnosed easily and can respond to continued supportive care.